Trade Causes Growth in Sub-Saharan Africa - Bruckner, Markus; Lederman, Daniel (World Bank, Washington, DC, 2014)
In the 1990s the mainstream consensus was that trade causes growth. Subsequent research shed doubt on the consensus view, as evidence suggested that the identification of the effect of trade on growth was problematic in the existing literature. This paper contributes to this debate by focusing on growth in Sub-Saharan Africa. It estimates the effect of openness to international trade on economic growth with panel data. Employing instrumental variables techniques that correct for endogeneity bias, the empirical evidence suggests that within-country variations in trade openness cause economic growth: a 1 percentage point increase in the ratio of trade over gross domestic product is associated with a short-run increase in growth of approximately 0.5 percent per year; the long-run effect is larger, reaching about 0.8 percent after ten years. These results are robust to controlling for country and time fixed effects as well as political institutions.